Physical activity ameliorates cartilage degeneration in a rat model of aging: A study on lubricin expression. Issue 2 (9th July 2014) - Musumeci, G.; Castrogiovanni, P.; Trovato, F. M.; Imbesi, R.; Giunta, S.; Szychlinska, M. A.; Loreto, C.; Castorina, S.; Mobasheri, A.
Abstract : Osteoarthritis (OA) is a common musculoskeletal disorder characterized by slow progression and joint tissue degeneration. Aging is one of the most prominent risk factors for the development and progression of OA. OA is not, however, an inevitable consequence of aging and age‐related changes in the joint can be distinguished from those that are the result of joint injury or inflammatory disease. The question that remains is whether OA can be prevented by undertaking regular physical activity. Would moderate physical activity in the elderly cartilage (and lubricin expression) comparable to a sedentary healthy adult? In this study we used physical exercise in healthy young, adult, and aged rats to evaluate the expression of lubricin as a novel biomarker of chondrocyte senescence. Immunohistochemistry and western blotting were used to evaluate the expression of lubricin in articular cartilage, while enzyme‐linked immunosorbent assay was used to quantify lubricin in synovial fluid. Morphological evaluation was done by histology to monitor possible tissue alterations. Our data suggest that moderate physical activity and normal mechanical joint loading in elderly rats improve tribology and lubricative properties of articular cartilage, promoting lubricin synthesis and its elevation in synovial fluid, thus preventing cartilage degradation compared with unexercised adult rats.